Evaluating the impacts of hydrologic and geomorphic alterations on floodplain connectivity. Issue 5 (22nd February 2017) - Stone, Mark C.; Byrne, Colin F.; Morrison, Ryan R.
Abstract: The dynamic interaction between a river and its floodplain is important for a variety of hydrologic, ecological, and geomorphic processes. However, water management activities have widely disrupted the natural flow regime and in many cases reduced floodplain connectivity. Recent environmental flow research has called for techniques that incorporate hydrogeomorphic processes, which are important for ecological and riverscape health. The objective of this study was to evaluate the impacts of hydrologic alterations on floodplain dynamics and connectivity. Changes in floodplain inundation dynamics and interface dynamics were investigated for 2 hydrologic scenarios on 2 distinct rivers—the Gila River and the Rio Grande, both in New Mexico, USA. The objective was achieved using a combination of 2‐D hydrodynamic models and analysis techniques to evaluate large spatial and temporal datasets. The results improved understanding of inundation patterns and water flux between the channel and floodplain under baseline and altered hydrologic scenarios. Due to the distinct qualities of the study sites, unique insights were gleaned. In the Gila River, discernible changes in floodplain dynamics were observed in spite of the relatively minor alterations from the baseline hydrologic conditions. In contrast, the Rio Grande results revealed the importance of not only hydrologic alterations but also channel incision on reduced floodplain connectivity. The proposed techniques can be adapted to a wide range of river systems depending on the nature of hydrologic or geomorphic alterations under consideration. As a result, the degree of alteration of floodplain connectivity can be better understood, leading to improved river management.